The Effect of Methanol Seed Kernel Extract of Mangifera Indica on Guinea Pig Tracheal Smooth Muscles - Etti, Imaobong Christopher; Akinniyi, Akinbola Lukuman; Johnny, Imoh Ime; Adedoyin, Adebayo Tologbonse (Biology, Medicine, & Natural Product Chemistry, 2025)
Mangifera indica, commonly known as mango, holds a revered position in traditional medicine for the numerous health benefits derived from different parts of the plant. The purpose of this study was to investigate the effect of methanol seed kernel extract of Magnifera indica on isolated guinea pig trachea. The acute toxicity profile was first evaluated as well as its phytochemical screening before exposing various concentrations of the methanol seed kernel extract to acetylcholine (Ach)-precontracted guinea pig tracheal rings. From the results, a dose of 5000mg/kg of the extract did not produce any form of toxicity. The presence of tannins, flavonoids and cardiac glycosides was revealed which probably fuels the medicinal properties of the seed kernel. Exposure of acetylcholine pre-contracted tracheal rings to different concentrations of the methanol kernel extract, resulted in a shift of the Ach dose response curve to the right but without achieving any maximum relaxation. There was no observed IC50 but rather an IC30 concentration was observed around 0.0013M. However, the observed minimal relaxation of Ach pre-contracted rings was not statistically significant (p>=0.5). It is possible that the observed minimal relaxation potential of the kernel extract coupled with its reported anti-inflammatory properties boosts its application in the relief of bronchial asthma claimed in ethnomedicine.